Undernutrition-induced stunting-like phenotype in Drosophila melanogaster - Putri, Tenri ZAD.; Wahyudin, Elly; Pratama, Muhammad R.; Fatiah, Dewita; Hardiyanti, Widya; Chaeratunnisa, Rizkya; Latada, Nadila P.; Fatmawati, Fatmawati; Mudjahid, Mukarram; Nainu, Firzan (Narra J, 2024)
Stunting resulting from undernutrition is a significant global health challenge, particularly in developing countries, yet its underlying mechanisms and consequences remain inadequately understood. This study utilizes Drosophila melanogaster as an in vivo model to investigate the molecular basis of stunting. Due to the conserved nature of signaling pathways between Drosophila and vertebrates, this organism serves as an effective model for studying growth disorders. The aim of this study was to establish a Drosophila model exhibiting a stunting-like phenotype and to elucidate the molecular mechanisms underlying this condition. The stunting phenotype was induced through dietary manipulation, involving a standard nutrient-rich diet (100%) and treatment diets with reduced concentrations of sucrose, glucose, yeast, and cornmeal at 50%, 25%, and 12.5%. Phenotypic assessments included measurements of larval body size, fecundity, survival rates, and locomotor activity, alongside molecular analyses of gene expression related to metabolism, cell proliferation, and survival, using RT-qPCR. Results demonstrated that undernutrition profoundly affected D. melanogaster, causing growth retardation, reduced larval body size, diminished fecundity, and lower survival rates, though locomotor function remained unaffected. Molecular analysis revealed a significant decrease in the expression of the totA gene and notable increases in the expression of dilp5, srl, and indy genes, with no significant changes observed in the expression of the pepck gene. These findings indicate that undernutrition induces a stunting-like phenotype, likely driven by alterations in the expression of genes associated with metabolism, cell proliferation, and survival. Overall, this study establishes D. melanogaster as a valuable in vivo model for studying stunting-like phenotypes resulting from nutritional deficiencies and provides insights into the molecular pathways involved in growth impairment.